The Main Problems of the Existing Systems of Labor Motivation of Civil Servants and the Prospects for Overcoming them - N. S. Pryazhnikov; M. V. Polevaya; E. V. Kamneva (Управленческие науки, 2017)
Introduction, Purpose. The research topicality is determined by the lack of systematization of the key problems associated with motivation, encouragement and reward for work that generates not only the decrease of production efficiency in different spheres, but also the increasing of workers dissatisfaction. Accordingly, the aim of the study is to analyze and synthesize the problems of motivating work motivation. And the more specific objectives of our research are focused on: 1) the selection of key subject areas; 2) specific analysis for each problematic direction, in particular, the polymotivation (mngoaspektnosti), lack of professional graphic study (as a basis for a better labor norming), according to the labor and implementation of the principle of fairness in the system of motivation, incentives and rewards for work. Methods.The main method of our research is theoretical and methodological analysis and synthesis of existing domestic and foreign research on the stated issues, supplemented by methods involving analysis, hermeneutics, social cultural and socio-economic implementation context of the principle of equity in different systems of motivation, incentives and rewards for work. Results. The main results (findings) of the study are: 1) the allocation of the most problematic areas analysis of imperfection of many existing motivation systems work, in particular: a) labor polymotivation, often distorting labor motivation, if managers and subordinate lose his labor relationship with the Organization and of the entire society values, dljakotorogo they employ; b) insufficient professional graphic study of the specific work, complicating the development of labor standards, loads of medical and hygiene restrictions, as well as on the relevant remuneration standards; in) ill-founded evaluation system; g) common disregard for the principle of equity in the systems of motivation, or a perverse interpretation. Discussion. We see the future of research in a more specific analysis, synthesis and building a clear typology (System) of the various problems associated with motivation, encouragement and reward for labor, in relation to specific organizations and labor posts. This, in our view, is essential not only to improving the activities in specific organizations, but also a kind of prevention of discontent by the work of individuals and entire communities, as well as prevention and reduction of general discontent at the level of the regions and the country as a whole.